Төв Азийн нүүдэлчдийн дунд угсаа-соёлын бүслэл тогтоосон нь - Дэлгэржаргал, Пүрэвсүрэн (Historia Mongolarum, 2003)
The up-to-date archeological, anthropological studies illustrates that from prehistoric times in Western and Mongolia cultivated the “hirgisur" rituals. Also the “square" tombs cultivated in the Easten parts of Mongolia. The two cultures belong to the particular ethnical gruops were inhabited in Mongolia at least 2000. The Central Asian cultural belt has already been formed in second millennium. Therefore, we conclude that it is obvious that the nomadic civilization based on livestock breeding formed al least in the third thousands BC.